Euglesa lindholmi Bespalaya & Vinarski & Aksenova & Babushkin & Gofarov & Kondakov & Konopleva & Kropotin & Mabrouki & Ovchankova & Palatov & Sokolova & Shevchenko & Travina & Taybi & Soboleva & Zubrii & Bolotov 2024, comb. nov. ... - Bespalaya, Yulia V.; Vinarski, Maxim V.; Aksenova, Olga V.; Babushkin, Evgeniy S.; Gofarov, Mikhail Yu.; Kondakov, Alexander V.; Konopleva, Ekaterina S.; Kropotin, Alexander V.; Mabrouki, Youness; Ovchankova, Nadezda B.; Palatov, Dmitry M.; Sokolova, Svetlana E.; et al. (Zenodo, 2023)
Euglesa lindholmi (Starobogatov & Streletzkaja, 1967) comb. nov. (Fig. 9C) Odhneripisidium lindholmi Starobogatov & Streletzkaja, 1967: 256, fig. 69. Type series: The holotype (a separate valve) and three separate valves of paratypes are deposited in ZIN, nos 1 and 2 in the systematic catalogue. Type locality: Russia, Republic of Yakutia (Sakha), Quaternary deposits on the left bank of the Allaikha River (Indigirka River Basin). Material examined: North Asia: Gydan Peninsula, VII.2017, Sokolova & Shevchenko leg., Republic of Yakutia, Yana River Basin, VIII.2019, Zubrii leg., Republic of Buryatia, near Vitim Nature Reserve, Dannoe Lake, VIII.2020, Babushkin leg., in total 29 specimens (lot nos RMBH MSph-737, MSph-370, MSph-569/1, MSph-569/2, MSph-572/1). Description: The shell is small (mean shell length ± SD 3.15 ± 0.03 mm), round-oval in shape (Fig. 9C). The beaks are rounded and prominent, and somewhat offset to the posterior edge of the valves (Fig. 9C). The cardinal tooth of the right valve ... : Published as part of Bespalaya, Yulia V., Vinarski, Maxim V., Aksenova, Olga V., Babushkin, Evgeniy S., Gofarov, Mikhail Yu., Kondakov, Alexander V., Konopleva, Ekaterina S., Kropotin, Alexander V., Mabrouki, Youness, Ovchankova, Nadezda B., Palatov, Dmitry M., Sokolova, Svetlana E., Shevchenko, Alexander R., Travina, Oksana V., Taybi, Abdelkhaleq F., Soboleva, Alena A., Zubrii, Natalia A. & Bolotov, Ivan N., 2024, Phylogeny, taxonomy, and biogeography of the Sphaeriinae (Bivalvia: Sphaeriidae), pp. 305-338 in Zoological Journal of the Linnean Society 201 (2) on pages 327-328, DOI: 10.1093/zoolinnean/zlad139, http://zenodo.org/record/13220074 ...